Ambiente laboral y organización del trabajo: modelo integrado que eleva la productividad en el sector agrícola (Estudios) - Pérez Corrales, Daniel Luis (2026)
This study analyzes the relationship between the work environment, work organization, and productivity at the Empresa Agroindustrial de Granos Sur del Jíbaro (EAIG Sur del Jíbaro) using a mixed approach that combines theoretical and empirical methods. A three-stage procedure was designed, starting with diagnosis (photocronometry and OTIDA diagram), treatment (salary restructuring, improvement of working conditions, and motivational actions), and feedback. The results showed that interventions focused on workplace well-being increased productivity by 139 %, tons processed by 139 %, and wages by 120 %, validating the null hypothesis (p=0.001) through a quasi-experimental design. The research highlights that there are determining factors for optimizing the work environment, such as fair remuneration, two-way communication, physical safety, and non-economic recognition. In addition, it was demonstrated that the integration of technical diagnostics with human resource strategies generates key synergies for productive efficiency. The study provides a replicable model for agricultural companies, emphasizing that multidimensional job satisfaction aligned with Maslow’s hierarchy of needs is essential for organizational stability and economic performance as a result of a good work environment. These findings underscore the importance of prioritizing human resources in agro-industrial environments, which drive sustainable results.